STRATEGI APPLE INC. DALAM PENGUASAAN PASAR PRODUK TEKNOLOGI DI INDONESIA TAHUN 2015-2019 - Irma Indrayani; Anggi Ramadhanty (Jurnal Ilmu dan Budaya, 2020)
The presence of Multinational Corporations (MNCs) is one of the impacts of the development of patterns of international relations after World War 2. MNCs become non-state actor which is considered to have a great influence on the international political economy. MNC itself is based in its home country and has subsidiaries or activities in other countries or we called host country. Indonesia has become one of the countries with potential markets chosen by various MNCs, and Apple Incorporation is one of them. Apple Inc. is one of the MNC from California, USA which is engaged in technology. The market in Indonesia is no doubt. Apple itself has a good image in Indonesian technology market. Various policies faced by Apple Inc. in Indonesia must be accepted in the interests of this company. In addition, Apple must be faced with competitors who also exist in the Indonesian technology market. Apple Inc. must have a strategy that can maintain its presence in Indonesia. So that it can continue to internationalize its products in the Indonesian technology market.